Hepatitis E–induced severe myositis. Issue 2 (24th November 2015) - Mengel, Annerose M.; Stenzel, Werner; Meisel, Andreas; Büning, Carsten
ABSTRACT: Introduction: Hepatitis E virus (HEV) is endemic in Asian and African countries but is rarely reported in Western countries. Although there are some prominent neurological manifestations, HEV is rarely recognized by neurologists. Methods: This is a case report of myositis induced by HEV. Results: We report the life‐threatening case of a 57‐year‐old man with flaccid tetraparesis due to myositis, acute hepatitis, and renal failure caused by HEV infection. Muscle biopsy revealed scattered myofiber necrosis with a diffuse, mild lymphomonocytic infiltrate in the endomysium and perimysium. Because the patient suffered from an acute HEV infection with a rapidly progressive course of severe myopathy, we started ribavirin treatment. He recovered partially within 3 weeks and recovered fully within 6 months. Conclusion: This case highlights a neurological manifestation of endemic HEV infection with severe myositis in a patient with alcoholic chronic liver disease. Ribavirin treatment is effective in severe HEV infection and may also lead to rapid neurological recovery. Muscle Nerve 53: 317–320, 2016